Fertility and pregnancy outcomes after uterine artery occlusion with or without myomectomy - Kun-Min Chang; Ming-Jer Chen; Ming-Huei Lee; Yuan-Der Huang; Chin-San Chen (Elsevier, 2012)
Uterine artery occlusion (UAO) is one of the minimally invasive procedures used to treat uterine fibroids. It has demonstrated the potential to reduce fibroid growth and related symptoms with few complications and adverse effects. Meanwhile, it may preserve the uterus and ovarian blood supply to allow pregnancy in women with symptomatic fibroids. Similarly, myomectomy is an alternative to hysterectomy in the treatment of symptomatic fibroids, especially for patients who want to maintain fertility. However, only few articles have focused on fertility and pregnancy outcomes after the combined procedures of UAO and myomectomy. We reviewed the effects of UAO with or without myomectomy on fertility and pregnancy outcomes by searching the MEDLINE biomedicine database, using uterine artery occlusion, myomectomy and pregnancy as key words. In conclusion, conception and term pregnancy were possible after these procedures, but evidence on whether risks of abortion and preterm birth have been increasing simultaneously remains inconclusive. Therefore, good counseling on benefits and risks of pregnancy outcomes before performing these procedures is mandatory.